The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.2106/jbjs.st.17.00044
|View full text |Cite
|
Sign up to set email alerts
|

A Posterior Approach to Open Reduction and Internal Fixation of Displaced Posterior Cruciate Ligament Tibial Osseous Avulsions

Abstract: The exact operative indications for PCL injuries remain in question, but we believe that displaced tibial avulsion injuries at the PCL attachment always require operative treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…A posterior approach to open reduction and internal fixation of PCL avulsion fractures was found to be effective in fractures involving large dislocations. 2 However, this method is highly invasive with a risk of neurovascular damage. Moreover, the fixation material was difficult to remove.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A posterior approach to open reduction and internal fixation of PCL avulsion fractures was found to be effective in fractures involving large dislocations. 2 However, this method is highly invasive with a risk of neurovascular damage. Moreover, the fixation material was difficult to remove.…”
Section: Discussionmentioning
confidence: 99%
“…Because the bone hole must be created with a 4.0-mm drill, this method is not indicated for patients with small bone fragments or crushing. Computed tomography (CT) scanning before surgery is required to assess the extent of dislocation and the size of bone fragments, as other surgical procedures may be optimal, including the pull-out technique 4 if the bone fragments are crushed, or the Burks approach 2 if the dislocation is very large ( Table 1 ).…”
Section: Indicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 The most common complications involve neurovascular injury resulting from access approach, loss of reduction, paresthesia, arthrofibrosis, or compression, which potentially causes pseudarthrosis and knee flexion contracture. [22][23][24] Willinger et al compared the open with an arthroscopic fracture treatment, and reported arthroscopic treatment may lead to a slightly higher subjective and objective outcome, but the rate of arthrofibrosis was slightly elevated in the arthroscopic group. 25 In this study, the bone healing was good without any neurovascular complications and knee stiffness; hence, this approach may be a safe and effective method.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Both open and arthroscopic procedures have been reported, and similar clinical results have been obtained. 2 , 3 Regarding open procedures, the fixation is direct and simple and there is no need for the learning curve of arthroscopic surgical procedures, 4 , 5 , 6 , 7 but these procedures are invasive. The advantage of arthroscopic procedures 8 , 9 , 10 is that the fracture can be directly exposed intra-articularly and combined intra-articular lesions can be treated simultaneously, in addition to their minimally invasive nature.…”
mentioning
confidence: 99%